Upregulation of Melanogenesis and Tyrosinase Activity: Potential Agents for Vitiligo - Niu, Chao (Molecules, 2017)
Melanin, the compound primarily responsible in humans for hair, eye and skin pigmentation, is produced by melanocytes through a complicated process called melanogenesis that is catalyzed by tyrosinase and other tyrosinase-related proteins. The abnormal loss of melanin causes dermatological problems such as vitiligo. Hence the regulation of melanogenesis and tyrosinase activity is very important for treating hypopigmentary disorders. Many melanogenesis stimulators have been discovered during the past decade. This article reviews recent advances in research on extracts and active ingredients of plants, synthesized compounds with stimulating effect on melanin synthesis and tyrosinase activity, as well as their influence on the expression of related proteins and possible signaling pathways for the design and development of novel anti-vitiligo agents.